Cool-feeling master batch as well as preparation method and application thereof
By hybridizing graphene and carbon nanotubes with boron nitride and adding modifiers to modify, a new cooling agent was prepared, which solved the problems of light absorption, heat generation and dispersion in the prior art, and significantly improved the Cooling coefficient and dispersion effect of textile fabrics.
Patent Information
- Application Number
- CN202411248212.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, after the introduction of graphene and carbon nanotubes into textile fabrics, the light absorption and heat generation effect is caused, which instead plays a role in keeping warm and insulated, and cannot effectively improve the cool feeling effect. At the same time, the dispersion and stability of high-thermal conductivity inorganic fillers are poor. Poor sex also affects the cooling effect.
A new cooling agent is prepared by hybridizing a small amount of carbon materials such as graphene, carbon nanotubes, and a powder mixture of carbon hybrid boron nitride is formed, and a modifier is added to modify it. The cooling agent improves its dispersion in the polyester and the perfection of the thermal network by ultrasonic hybridization and grinding to a suitable particle size.
It significantly improves the cool feeling coefficient of textile fabrics, enhances the dispersion and compatibility of boron nitride in polyester, thereby greatly improving the dispersion effect of coolant in the cool masterbatch and fibers, achieving better cooling Feeling effect.
Smart Images

Figure CN119505486A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of textiles, and in particular to a cooling masterbatch and a preparation method and application thereof. Background Art
[0002] Polyester fiber, commonly known as polyester, is widely used in textile and clothing manufacturing due to its excellent wrinkle resistance, light resistance, acid resistance, alkali resistance, high strength and low price, which brings a lot of convenience to our daily life. Because polyester fiber has poor moisture absorption and poor thermal conductivity, people will feel stuffy and uncomfortable wearing clothes made of polyester fiber textile fabrics in summer. At present, physical blending modification is often used - introducing high thermal conductivity materials into polyester fibers to improve the thermal conductivity efficiency to achieve the cooling effect of the fabric.
[0003] At present, commonly used high thermal conductivity materials are mostly high thermal conductivity powders, such as high thermal conductivity powders including jade powder, aluminum nitride and newly developed boron nitride. However, high thermal conductivity powders are not resistant to water washing and are easy to fall off. The invention patent application publication number is CN 108794997 A, a cool masterbatch, a cool fiber and its preparation method and use, which discloses a cool masterbatch, a cool fiber and its preparation method and use, a cool masterbatch including a substrate, and a graphene material and jade powder dispersed in the substrate, wherein the substrate includes any one or a combination of at least two of a polyester material, a nylon material and a polypropylene material, graphene and jade powder are added to the fiber substrate at the same time, mixed to obtain functional particles, and then the two are mixed with a blank fiber substrate. Although mixing graphene and jade powder can improve the problem that jade powder is not resistant to water washing and is easy to fall off. However, graphene belongs to carbon materials, and in addition to having high thermal conductivity, it also has the effect of absorbing light and generating heat. When the added graphene content is 0.1% or even 0.05%, the textile fabric has a high light absorption and heat generation effect. During daytime outdoor activities, the corresponding fibers / textiles will absorb light and generate heat, causing the temperature of the clothing to be higher than the body heat. At this time, the high thermal conductivity will have the opposite effect and will conduct the heat to the human body, thereby achieving a heat preservation and warming effect, so that the cooling effect cannot be further improved.
[0004] In recent years, high thermal conductivity inorganic fillers have also been used, such as nitride inorganic filler systems (BN, AlN and Si3N4, etc.), oxide inorganic filler systems (Al2O3, MgO, and BeO, etc.), carbide systems (SiC, GO, CNT, Diamond, CNF, etc.) and metal ions (Ag / Cu / Zn), etc. However, high thermal conductivity inorganic fillers have the problems of easy uneven dispersion, easy agglomeration and poor stability. For example, a polyester fiber with an invention patent application publication number of CN 104178840 A discloses adding boron nitride inorganic particles with an average particle size of 0.1-1.0 microns to a polyester polymer, so that the polyester fiber has a cool feeling and maintains good tensile strength. Even if the above technical solution uses boron nitride with the highest thermal conductivity to modify the polyester fiber, the coolness coefficient of the fabric woven by the pure modified polyester fiber is still lower than that of fabrics made of other materials, and the coolness coefficient is below 0.2. Experiments have found that when boron nitride powder is used as a cooling agent, when 0.6-1% boron nitride is added to textile fabrics, the cooling coefficient is 0.18-0.19 J / (cm2·s), and the cooling effect cannot be further improved.
[0005] Therefore, there is a need in the art to develop a material with an obvious cool feeling to solve the problems of light absorption, heat generation, and difficulty in dispersion of materials such as graphene and carbon nanotubes. Summary of the invention
[0006] In view of the above problems, the present application provides a cooling masterbatch and its preparation method and application. The cooling masterbatch hybridizes boron nitride with a small amount of carbon materials such as graphene and carbon nanotubes to improve the thermal conductivity of the boron nitride material while eliminating the absorption of visible light, near-infrared and even ultraviolet light by graphene and carbon nanotubes, that is, the heat-generating effect of light absorption. At the same time, the graphene and carbon nanotube layers are inserted into the boron nitride through ultrasonic hybridization, and then ground to a suitable particle size, so that the boron nitride has a better dispersion effect and a more complete thermal conductive network compared to the processing method of directly adding a dispersant, thereby greatly improving the dispersion effect of the cooling masterbatch and the cooling agent in the fiber.
[0007] To achieve the above-mentioned purpose, in the first aspect, the inventor provides a cooling masterbatch, which is formed by melt extrusion granulation of a mixture of polyester and a cooling agent, wherein the mass ratio of the polyester to the cooling agent is 70-90:10-30; the cooling agent is obtained by adding a modifier to a powder mixture of carbon hybridized boron nitride obtained by hybrid drying including a carbon material and boron nitride; the mass ratio of the carbon material to the boron nitride is 98-99.9:0.1-1.
[0008] Different from the prior art, the cooling agent of the present invention is prepared by hybridizing boron nitride and carbon material in a mass ratio of 98 to 99.9: 0.1 to 1 to obtain carbon hybridized boron nitride, and adding a modifier for modification. Hybridizing boron nitride with a small amount of carbon materials such as graphene and carbon nanotubes improves the thermal conductivity of the boron nitride material while eliminating the absorption of graphene and carbon nanotubes to visible light, near-infrared and even ultraviolet light, that is, the effect of absorbing light and heating. This is because graphene and carbon nanotubes are inserted between boron nitride sheets with few layers / few walls or even single layers, and because white boron nitride has a high reflectivity for visible light, it blocks the absorption of visible light by the carbon material. During daytime outdoor activities, when the content of carbon material in the cooling agent is too high, it will have a negative impact on the thermal conductivity of boron nitride, because the carbon material itself has the effect of absorbing light and heating. In addition, excessively high carbon material content may also affect the uniformity and stability of the cooling agent, further affecting its cooling effect.
[0009] As an embodiment of the present invention, the modifier is any one of octadecylamine, stearic acid and silane coupling agent. Further, the content of the modifier is 0.1-2%wt% of the carbon hybridized boron nitride.
[0010] In this way, the cooling coefficient of textile fabrics is improved. When the average particle size of boron nitride is 500nm, the nanoparticles are easy to agglomerate and have poor compatibility with polyester. Therefore, the direct addition of boron nitride and carbon-hybridized boron nitride has poor dispersibility in masterbatch and fiber, thus affecting heat conduction. The carbon-hybridized boron nitride modified with octadecylamine, stearic acid and silane coupling agent, i.e., the cooling agent, can greatly improve the dispersibility of boron nitride in polyester and its compatibility with polyester, thereby synergistically increasing the instantaneous cooling coefficient of the corresponding textile fabrics.
[0011] As an embodiment of the present invention, the carbon material is at least one of graphene and carbon nanotubes.
[0012] In this way, the thermal conductivity of boron nitride is improved to increase the cooling effect of the fabric.
[0013] As an embodiment of the present invention, the particle size of the cooling agent is 200nm-1.5um, or the particle size of the polyester is 50-60 mesh. Preferably, the particle size of the cooling agent is 400nm-1um.
[0014] To achieve the above object, in a second aspect, the inventor provides a method for preparing a cooling masterbatch, comprising the following steps:
[0015] The carbon material and boron nitride are hybridized and dried in a mass ratio of 98-99.9:0.1-1 to obtain a powder mixture, which is added into a modifier solution, mixed and dried to obtain a cooling agent;
[0016] The cooling agent and the polyester are dry-mixed in a mass ratio of 10-30:70-90, melted, and extruded into granules.
[0017] Furthermore, the carbon material and boron nitride are hybridized and dried at a mass ratio of 98-99.9:0.1-1 to obtain a powder mixture, and the mixture is added to a modifier solution, mixed and dried to obtain a cooling agent, which specifically includes:
[0018] Preparation: weigh the carbon material and boron nitride in proportion and put them into containers filled with anhydrous ethanol respectively;
[0019] Dispersion: ultrasonically treat the carbon material and boron nitride in the container for 2 to 5 minutes respectively to obtain a carbon material dispersion and a boron nitride dispersion;
[0020] Hybridization: mixing the carbon material dispersion and the boron nitride dispersion, adding anhydrous ethanol, and ultrasonically hybridizing for 10 to 30 minutes to obtain a hybrid dispersion;
[0021] Drying and grinding: After distilling the hybrid dispersion and drying it, grinding it to obtain a powder mixture;
[0022] Modification: put the above powder mixture into a corresponding dosage of the modifier solution, stir evenly, and obtain a mixed liquid;
[0023] Grinding and drying: Add the above mixed liquid into the mixture and grind it, then use spray drying to obtain the cooling agent.
[0024] Furthermore, the cooling agent and the polyester are dry mixed in a mass ratio of 10-30:70-90, melted, and extruded into granules, which specifically includes:
[0025] Weighing and drying: weigh the polyester and the cooling agent in proportion, dry the polyester at 180°C for 4 hours, and vacuum dry the cooling agent at 80°C for 4 hours;
[0026] Mixing: Put the dried polyester and cooling agent into a mixer and stir at a stirring rate of 100 r / min for 5 minutes to obtain a uniform mixture;
[0027] Extrusion granulation: Add the above-mentioned mixed material into a twin-screw extruder for melting, extrusion granulation, and obtain a cooling masterbatch, wherein the cooling temperature is 15-30°C, the speed of the twin-screw extruder is 500r / min, the screw extrusion temperature is set to 120°C-180°C-220°C-240°C-245°C-260°C in sequence, and the melt temperature is controlled between 260 and 280°C.
[0028] In this way, in the process of making the cooling agent, the carbon material can be easily dispersed into the boron nitride through the dispersion and hybridization of the solution. At the same time, under the action of the modifier, the compatibility between boron nitride and polyester can be enhanced, so that the boron nitride has a better dispersion effect and a more perfect thermal conductive network compared to the processing method of directly adding the dispersant, thereby greatly improving the dispersion effect of the cooling agent in the cooling masterbatch and the fiber.
[0029] To achieve the above-mentioned purpose, in a third aspect, the inventor provides a cooling polyester fiber, which is obtained by spinning a melt obtained by melt-blending polyester chips and cooling masterbatch.
[0030] In this way, the amount of raw material added is determined online by a meter, the dried polyester chips are added through the main feed port, the dried cool masterbatch is metered and added through the side feed port, melt blended and extruded, and the melt is spun through a spinneret to obtain cool polyester fibers.
[0031] To achieve the above-mentioned purpose, in a fourth aspect, the inventor provides a cool polyester fiber fabric, which is spun from cool polyester fibers.
[0032] The prepared cool polyester fiber is combed, 3 to 5 slivers are combined, the coarse yarn drafting multiple is 6 times, the fine yarn spindle speed is 15000rpm, and the fine yarn is used as warp yarn and weft yarn respectively. The warp yarn and the weft yarn are alternately woven to form a cool polyester fiber fabric.
[0033] The above-mentioned records related to the invention content are only an overview of the technical solution of the present application. In order to enable ordinary technicians in the field to more clearly understand the technical solution of the present application, and then implement it according to the text of the specification and the contents recorded in the drawings, and to make the above-mentioned purpose and other purposes, features and advantages of the present application easier to understand, the following is an explanation in combination with the specific implementation mode and drawings of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings are only used to illustrate the principles, implementation methods, applications, characteristics and effects of the specific embodiments of the present application and other related contents, and shall not be considered as limitations of the present application.
[0035] In the drawings of the specification:
[0036] Figure 1 This is a general flow chart for preparing a cooling masterbatch for this application;
[0037] Figure 2 This is a flow chart of the specific steps for preparing a cooling agent according to the present application;
[0038] Figure 3 This is a flow chart of the specific steps for preparing a cooling masterbatch for this application. DETAILED DESCRIPTION
[0039] In order to explain in detail the possible application scenarios, technical principles, specific schemes that can be implemented, and the purposes and effects that can be achieved, the following is a detailed description of the specific embodiments listed in conjunction with the accompanying drawings. The embodiments described herein are only used to more clearly illustrate the technical solutions of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0040] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.
[0041] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0042] The following detailed description specifically discloses the embodiments of the present application with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0043] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0045] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0046] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0047] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0048] The terms "above" and "below" used in this application include the number, for example, "one or more" means one or more, and "one or more of A and B" means "A", "B" or "A and B".
[0049] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0050] Unless otherwise stated, contents and percentages throughout the present application are based on mass.
[0051] The first aspect of the present invention provides a cooling masterbatch, which is formed by mixing and melt-extruding a polyester and a cooling agent, wherein the mass ratio of the polyester to the cooling agent is 70-90:10-30; the cooling agent is obtained by mixing and hybridizing a carbon material and boron nitride to obtain a carbon hybridized boron nitride powder mixture, and then adding a modifier to modify the mixture; the mass ratio of the carbon material to the boron nitride is 98-99.9:0.1-1.
[0052] Physical blending modification is to introduce powders with high thermal conductivity to improve the thermal conductivity of polyester fiber itself, so as to achieve instant cooling effect. Commonly used powders are jade powder, aluminum nitride and boron nitride. The cooling coefficient of the modified textile fabrics increases successively. Even if boron nitride with the highest thermal conductivity is used to modify polyester fiber, the cooling coefficient of the fabric woven by pure modified polyester fiber is still lower than that of other materials, and the cooling coefficient is 0.2J / (cm 2 ·s) and below, in order to further improve the coolness coefficient of the boron nitride powder modified fiber, the thermal conductivity coefficient and dispersibility of the boron nitride powder in the matrix can be improved by modification, thereby improving the coolness coefficient of the fabric.
[0053] In addition to high thermal conductivity, carbon materials also have the effect of absorbing light and generating heat. During outdoor activities during the day, the corresponding fibers / textiles will absorb light and generate heat, causing the temperature of the clothing to be higher than the body temperature. At this time, the high thermal conductivity will have the opposite effect, transferring heat to the human body, thereby achieving a heat preservation effect, but not a cooling effect. Therefore, simply adding a mixture of carbon materials and boron nitride as a high thermal conductivity filler to textile fabrics will hardly achieve a cooling effect when outdoors.
[0054] Different from the prior art, the cooling agent of the present invention is a carbon-hybridized boron nitride obtained by hybridizing boron nitride and carbon material in a mass ratio of 98 to 99.9: 0.1 to 1, and a modifier is added for modification. A small amount of carbon materials such as graphene and carbon nanotubes are hybridized with boron nitride to improve the thermal conductivity of the boron nitride material while eliminating the absorption of graphene and carbon nanotubes to visible light, near-infrared and even ultraviolet light, that is, the effect of absorbing light and heating. This is because graphene and carbon nanotubes are inserted between boron nitride sheets with few layers / few walls or even single layers, and because white boron nitride has a high reflectivity for visible light, it blocks the absorption of visible light by the carbon material. During daytime outdoor activities, when the content of carbon material in the cooling agent is too high, it will have a negative impact on the thermal conductivity of boron nitride, because the carbon material itself has the effect of absorbing light and heating. In addition, excessively high carbon material content may also affect the uniformity and stability of the cooling agent, further affecting its cooling effect.
[0055] According to some embodiments of the present application, the modifier is any one of octadecylamine, stearic acid and a silane coupling agent. Further, the content of the modifier is 0.1 to 2% by weight of the carbon-hybridized boron nitride.
[0056] In this way, the cooling coefficient of textile fabrics is improved. When the average particle size of boron nitride is 500nm, the nanoparticles are easy to agglomerate and have poor compatibility with polyester. Therefore, the direct addition of boron nitride and carbon-hybridized boron nitride has poor dispersibility in masterbatch and fiber, thus affecting heat conduction. The carbon-hybridized boron nitride modified with octadecylamine, stearic acid and silane coupling agent, i.e., the cooling agent, can greatly improve the dispersibility of boron nitride in polyester and its compatibility with polyester, thereby synergistically increasing the instantaneous cooling coefficient of the corresponding textile fabrics.
[0057] Octadecylamine is a long-chain alkylamine. Octadecylamine can physically adsorb to the surface of boron nitride through its long-chain alkyl group, reduce the surface energy, and thus help disperse boron nitride in the polymer matrix. The addition of octadecylamine can improve the compatibility between boron nitride and polymer, reduce agglomeration, and improve the uniformity of dispersion of boron nitride in polymer.
[0058] As a fatty acid, stearic acid chemically adsorbs on the surface of boron nitride through its carboxyl group to form a stable bond, thereby enhancing the interaction between boron nitride and the polymer. This chemical bond helps to improve the dispersion stability of boron nitride in the polymer and prevent it from reaggregating.
[0059] Silane coupling agent is an organosilicon compound with two different reactive groups, which can form an organosilicon film on the surface of boron nitride, thereby improving the interfacial compatibility between boron nitride and polymer. The mechanism of action of silane coupling agent is that part of its groups react with the surface of boron nitride, and the other part of its groups react with the polymer to form an inorganic phase-silane coupling agent-organic phase bonding layer, thereby improving the dispersibility and bonding strength of boron nitride in the polymer. Octadecylamine, stearic acid and silane coupling agent promote the dispersion of boron nitride in cooling masterbatch through different mechanisms of action. Octadecylamine mainly improves dispersibility through physical adsorption, stearic acid enhances stability through chemical adsorption, and silane coupling agent improves interfacial compatibility by forming an inorganic phase-organic phase bonding layer. The rational use of these additives plays an important role in improving the dispersibility and overall performance of boron nitride in polymer thermal conductive composite materials.
[0060] According to some embodiments of the present application, the carbon material is at least one of graphene and carbon nanotubes.
[0061] In this way, the thermal conductivity of boron nitride is improved to increase the cooling effect of the fabric.
[0062] Graphene is a planar film composed of carbon atoms in a hexagonal honeycomb lattice with SP2 hybrid orbitals. It is a two-dimensional material with a thickness of only one carbon atom. The thermal conductivity of graphene can reach 3000-5000w / (m·k), and the thermal conductivity of carbon nanotubes is also as high as 3000w / (m·k), both of which are far higher than the thermal conductivity of hexagonal boron nitride. From the perspective of heat conduction, adding graphene and carbon nanotubes can increase the thermal conductivity of the fabric to achieve a cooling effect. In order to improve the thermal conductivity of boron nitride, graphene, carbon nanotubes and other substances can be used to modify boron nitride.
[0063] According to some embodiments of the present application, the particle size of the cooling agent is 200nm-1.5um, or the particle size of the polyester is 50-60 mesh. Preferably, the particle size of the cooling agent is 400nm-1um.
[0064] The present application also provides a method for preparing a cooling masterbatch. Figure 1 As shown, the following steps are included:
[0065] S1 carbon material and boron nitride are hybridized and dried in a mass ratio of 98-99.9:0.1-1 to obtain a powder mixture of carbon hybridized boron nitride, which is added to a modifier solution, mixed and dried to obtain a cooling agent;
[0066] S2: dry-mix the cooling agent and the polyester in a mass ratio of 10-30:70-90, melt, and extrude to form granules.
[0067] Further, such as Figure 2As shown, the carbon material and boron nitride are hybridized and dried in a mass ratio of 98-99.9:0.1-1 to obtain a powder mixture of carbon hybridized boron nitride, and the mixture is added to a modifier solution, mixed and dried to obtain a cooling agent, which specifically includes the following steps:
[0068] S11. Material preparation: weigh the carbon material and boron nitride in proportion, and put them into containers filled with anhydrous ethanol respectively;
[0069] S12. Dispersion: using an ultrasonic cell disruptor for 2 to 5 min, with an ultrasonic amplitude of Φ15, an ultrasonic time of 3.5 s, and a gap of 1.5 s to obtain a carbon material dispersion and a boron nitride dispersion;
[0070] S13. Hybridization: Mix the above dispersions, add anhydrous ethanol, and perform ultrasonic hybridization for 10 to 30 minutes using an ultrasonic cell disruptor to obtain a hybrid dispersion;
[0071] S14. Dry grinding: distill the solvent in the hybrid dispersion at 60-70°C using a rotary evaporator to obtain a dry powder, add the hybrid powder and 20 parts by weight of dry ice into a German FRITSCH planetary ball mill, and grind at a speed of 400-500 rpm for 2-6 hours until the appropriate particle size is obtained;
[0072] S15. Modification: First weigh the corresponding amount of modifier, add it into water and stir to disperse it evenly, then add the ground hybrid powder into the above dispersion and continue heating and stirring for 0.5 to 2 hours, with the stirring temperature at 50 to 100°C.
[0073] S16. Grinding and drying: Add the above mixed liquid into a ball mill for grinding, and then use spray drying to obtain a cooling agent.
[0074] Further, such as Figure 3 As shown, the specific steps of dry mixing, melting and granulating the cooling agent and the polyester in a mass ratio of 10-30:70-90 include:
[0075] S21 weighing and drying: weigh the polyester and the cooling agent in proportion, dry the polyester at 180 ° C for 4h, and dry the cooling agent at 80 ° C for 4h in vacuum;
[0076] S22 mixing: The dried polyester and cooling agent were placed in a mixer and stirred at a stirring rate of 100r / min for 5min to obtain a uniform mixture;
[0077] S23. Extrusion granulation: Add the above-mentioned mixed material into a twin-screw extruder for melting, extrusion granulation, and obtain a cooling masterbatch, wherein the cooling temperature is 15-30°C, the speed of the twin-screw extruder is 500r / min, the screw extrusion temperature is set to 120°C-180°C-220°C-240°C-245°C-260°C in sequence, and the melt temperature is controlled between 260 and 280°C.
[0078] In this way, in the process of making the cooling agent, the carbon material can be easily dispersed into the boron nitride through the dispersion and hybridization of the solution. At the same time, under the action of the modifier, the compatibility between boron nitride and polyester can be enhanced, so that the boron nitride has a better dispersion effect and a more perfect thermal conductive network compared to the processing method of directly adding the dispersant, thereby greatly improving the dispersion effect of the cooling agent in the cooling masterbatch and the fiber.
[0079] In order to make the polyester with inorganic powder have good spinnability, the particle size of the inorganic powder needs to be controlled within 3um. However, due to its unique toughness, it is difficult to directly grind the graphene material to a particle size of about 3um. At the same time, graphene and carbon nanotubes are very easy to agglomerate, and it is difficult to prepare high-concentration and uniformly dispersed masterbatches for polyester fibers. Among them, graphene is easy to agglomerate and difficult to peel off, so it is difficult to prepare small-particle graphene materials suitable for long-fiber spinning. However, it is relatively easy to disperse in solution. First, the graphene and carbon nanotube layers are inserted into the boron nitride through ultrasonic hybridization, and then ground to a suitable particle size, because a single h-BN basal plane is composed of alternating boron (B) atoms and nitrogen (N) atoms, in which B and N atoms are connected by strong covalent bonds. The h-BN layers are stacked in an AA' type, and the B atoms on the c-axis are stacked alternately opposite to the N atoms, with an interlayer spacing of 0.333nm. The difference in electronegativity between B and N atoms makes the h-BN layers have some ionic bonding properties in addition to the van der Waals force, which is called the "Lip-Lip" effect. The interaction between the boron nitride layers is stronger, and boron nitride is relatively hard, which also partially acts as a grinding medium, making it easier to grind graphene into smaller particles.
[0080] The present application also provides a cool polyester fiber, which is obtained by melt-blending polyester chips and cool masterbatch to obtain a melt, and then spinning the melt.
[0081] The amount of raw material added is determined online by a meter, and the dried polyester chips are added through the main feeding port, and the dried cooling masterbatch is metered and added through the side feeding port, melt blended and extruded, and the melt is spun through a spinneret to obtain cooling polyester fibers. Among them, the mass ratio of polyester chips to cooling masterbatch is 98:2, that is, the cooling agent content is 0.4%.
[0082] The present application also provides a cool polyester fiber fabric, which is spun from cool polyester fibers.
[0083] The prepared cool polyester fiber is combed, 3 to 5 slivers are combined, the coarse yarn drafting multiple is 6 times, the fine yarn spindle speed is 15000rpm, and the fine yarn is used as warp yarn and weft yarn respectively. The warp yarn and the weft yarn are alternately woven to form a cool polyester fiber fabric.
[0084] All raw materials in this embodiment are commercially available. Graphene was purchased from Wuxi Enyuan Technology Co., Ltd., D50 = 2um, boron nitride was purchased from Shanghai Maoguo Nano Technology Co., Ltd., D50 = 500nm; octadecylamine (ODA) was purchased from Shanghai Langkang Biotechnology Co., Ltd., Indonesian Green Treasure Stearic Acid 1801 was purchased from Guangdong Xinrunhao Chemical Co., Ltd., silane coupling agent selected Dow Corning model z-6172, namely vinyl tris (2-methoxyethoxy), silane was purchased from Suzhou Sipai New Materials Co., Ltd.
[0085] Example 1 Preparation of a Cooling Masterbatch, Fiber and Fabric
[0086] 1. Cooling masterbatch, including polyester and cooling agent mixed melt extrusion granulation molding, the mass ratio of polyester and cooling agent is 80:20, the cooling agent is carbon material, boron nitride with a mass ratio of 99.5:
[0087] 0.5 hybridization to obtain carbon hybridized boron nitride, which is modified by adding a modifier. The boron nitride is hexagonal boron nitride nanosheets (h-BNNSs), the selected carbon material is graphene, the modifier is octadecylamine, and the content of the modifier is 1% of the carbon hybridized boron nitride.
[0088] 2. A preparation of a cooling masterbatch, including the preparation of a cooling agent and the preparation of a cooling masterbatch. The preparation of the cooling agent includes the following steps:
[0089] Weighing: Weigh graphene (0.5 g) and boron nitride (9.95 g) in proportion, and use anhydrous ethanol as a solvent to prepare dispersions with concentrations of 0.05 (wt)% and 2 (wt)% respectively;
[0090] Dispersion: Graphene and boron nitride were added to containers containing ethanol respectively, and then ultrasonicated for 2 to 5 minutes using an ultrasonic cell disruptor, with an ultrasonic amplitude of Φ15, an ultrasonic time of 3.5 seconds, and an interval of 1.5 seconds, to prepare dispersions with a volume fraction of 0.025 (wt)% (200 ml) and 1.98% (500 ml), respectively;
[0091] Hybridization: Pour the graphene dispersion into the boron nitride dispersion, add an appropriate amount of ethanol to make the volume 1000 ml, and then continue ultrasonic hybridization for 20 minutes using an ultrasonic cell disruptor;
[0092] At 70° C., the solvent in the hybridized dispersion was distilled off using a rotary evaporator to obtain a dry powder;
[0093] Repeat steps S1 to S4 until 1 kg of hybrid powder is obtained;
[0094] Grinding: The hybrid powder and 20 parts by weight of dry ice were added into a German FRITSCH planetary ball mill and ground at a speed of 500 rpm for 3 h until the average particle size was 500 nm.
[0095] Modification: First, weigh a corresponding amount of the modifier octadecylamine and add it into water and stir to disperse it evenly. Then, add the ground hybrid powder into the above dispersion and continue to heat and stir for 2 hours at a stirring temperature of 50-100°C. Then, add the mixed liquid into a planetary ball mill in batches and grind for 40 minutes. Then, spray dry the mixture to obtain the cooling agent.
[0096] On the basis of the above preparation of the cooling agent, further preparing the cooling masterbatch includes the following specific steps:
[0097] Weighing: weigh each component according to the formula of cooling masterbatch;
[0098] Drying: The polyester chips were dried by air blast at 180°C for 4 hours; the cooling agent was vacuum dried at 80°C for 4 hours;
[0099] Mixing: Put the dried materials, i.e. polyester and cooling agent, into a mixer and stir at a stirring rate of 100 r / min for 5 minutes to mix evenly;
[0100] Extrusion granulation: Add the mixed material into the twin-screw extruder for melt extrusion granulation to make high-performance cooling masterbatch, where the cooling temperature is 15-30℃ and the twin-screw extruder speed is
[0101] 500r / min, screw extrusion temperature is set to 120℃-180℃-220℃
[0102] -240℃-245℃-260℃, the melt temperature is controlled between 260~280℃.
[0103] 3. Preparation of cool fiber:
[0104] The amount of raw material added is determined online by a meter, and the dried polyester chips are added through the main feeding port, and the dried high-performance cooling functional masterbatch is metered and added through the side feeding port, melt blended and extruded, and the melt is spun through a spinneret to obtain cooling polyester fiber. Among them, the mass ratio of polyester chips to cooling functional masterbatch is 98:2, that is, the cooling agent content is 0.4%.
[0105] 4. Preparation of cool polyester fiber fabric:
[0106] The prepared cool polyester fiber is combed, 3 to 5 slivers are combined, the coarse yarn drafting multiple is 6 times, the fine yarn spindle speed is 15000rpm, and the fine yarn is used as warp yarn and weft yarn respectively. The warp yarn and the weft yarn are alternately woven to form a cool polyester fiber fabric.
[0107] The mass ratio of boron nitride to graphene in the cooling agent of Example 1 is 9.5:0.5, and the mass ratio of the cooling fiber in the polyester chips to the cooling masterbatch is 98:2, that is, the cooling agent content is 0.4%, and the modifier is octadecylamine.
[0108] Example 2
[0109] The difference between this embodiment and embodiment 1 is that the mass ratio of boron nitride to graphene in the cooling agent is 99:1, and the mass ratio of cooling fiber in polyester chips to cooling masterbatch is 97:3, that is, the content of cooling agent is 0.6%.
[0110] Example 3
[0111] The difference between this embodiment and embodiment 1 is that the modifier used for the cooling agent is stearic acid.
[0112] Example 4
[0113] The difference between this embodiment and embodiment 1 is that the cooling agent used is silane coupling agent Z-6172.
[0114] Example 5
[0115] The difference between this embodiment and embodiment 1 is that the mass ratio of the cooling fiber in the polyester chips to the cooling masterbatch is 97:3, that is, the content of the cooling agent is 0.6%.
[0116] Comparative Example 1
[0117] The difference between this comparative example and Example 1 is that the modifier in the cooling masterbatch is changed to boron nitride.
[0118] Comparative Example 2
[0119] The difference between this comparison and Example 1 is that the cooling agent in the masterbatch is replaced by graphene.
[0120] Comparative Example 3
[0121] The difference between this comparative example and Example 1 is that the cooling agent is changed to a blend of boron nitride and graphene, and the mass ratio of boron nitride to graphene is 99:1.
[0122] Comparative Example 4
[0123] The difference between this comparative example and Example 1 is that the mass ratio of boron nitride to graphene in the cooling agent is 97:3.
[0124] Comparative Example 5
[0125] This comparative example is different from Example 1 in that the cooling agent is replaced by graphene hybridized boron nitride, no modifier is used for treatment, and the mass ratio of boron nitride to graphene is 99.5:0.5.
[0126] Performance testing:
[0127] 1. Dispersion test of functional additives in polymers
[0128] There are three methods for determining the dispersibility of inorganic powders in polymers, namely the two-roller method, the filter pressure rise method, and the thin film method. In this technical solution, the masterbatch is mainly used to produce the corresponding polyester fiber through melt spinning, so the filter pressure rise method is used for testing.
[0129] Test principle: The increase in the internal melt pressure of the extruder caused by the clogging of the filter screen when the masterbatch passes through the filter screen of the extruder is a measure of the dispersion of the anti-ultraviolet nano-oxide. Filter pressure rise value (FPV) definition: the pressure value increased by each gram of inorganic powder during extrusion. The test results of the cooling masterbatch filtration performance are shown in Table 1.
[0130] Table 1 Filterability test results
[0131] name Filter screen accuracy (mesh) Filtration pressure difference (MPa) Example 1 1500 0.0302 Example 2 1500 0.0280 Example 3 1500 0.0325 Example 4 1500 0.0260 Comparative Example 1 1500 0.181 Comparative Example 2 1500 0.060 Comparative Example 3 1500 0.320 Comparative Example 4 1500 0.0282 Comparative Example 5 1500 0.190
[0132] As can be seen from Table 1, the cooling modifiers in the cooling masterbatches prepared in Examples 1 to 4 and Comparative Example 4 are uniformly dispersed and can be used in the form of polyester fibers, and the filtration pressure differences are all less than 0.05.
[0133] The filtration pressure difference of Comparative Examples 1 to 3 and Comparative Example 5 is greater than 0.05, indicating that the dispersibility of the inorganic powder in the masterbatch is poor, which may cause blockage of the spinneret when used for melt spinning of polyester fibers. The filtration pressure difference of Comparative Example 2 is 0.06, which is much smaller than Comparative Examples 1, 3 and 5. This is because the smaller the particle size, the easier it is to agglomerate and the worse the dispersion performance.
[0134] By comparing Examples 1 to 4 and Comparative Example 5, it can be found that the dispersibility of inorganic powder boron nitride in polyester can be improved by using octadecylamine (OD), stearic acid and coupling agent. Among them, octadecylamine and stearic acid are used to modify boron nitride using the Lewis acid-base principle, and the silane coupling agent belongs to non-covalent functionalization modification, which is mainly physical coating, and will not significantly change the spatial shape properties of the nanomaterial structure during the functionalization process, and can maintain the inherent properties.
[0135] 2. Cooling performance test
[0136] According to the national standard “GB / T 35263-2017 Testing and Evaluation of Instantaneous Cooling Properties of Textiles upon Contact”, the cooling coefficients of each group of samples and the fabrics after washing 100 times were measured. The test results are shown in Table 2.
[0137] Table 2 Detection effect of coolness coefficient
[0138] name <![CDATA[Cooling coefficient (before washing), J / (cm 2 ·s)]]> <![CDATA[Cooling coefficient (after 100 washes), J / (cm 2 ·s)]]> Example 1 0.23 0.22 Example 2 0.24 0.23 Example 3 0.21 0.21 Example 4 0.25 0.25 Example 5 0.26 0.25 Comparative Example 1 0.16 0.15 Comparative Example 2 0.20 0.20 Comparative Example 3 0.14 0.14 Comparative Example 4 0.25 0.24 Comparative Example 5 0.18 0.17
[0139] It can be seen from Table 2 that when pure boron nitride is used as a cooling agent in Examples 1 to 5, the instantaneous cooling coefficient is greatly improved, and the cooling effect is significantly increased. By comparing Example 1, Comparative Example 1 and Comparative Example 5, it can be found that graphene hybridized boron nitride can improve its thermal conductivity, thereby improving the instantaneous cooling coefficient of the fabric, but the hybrid powder that has not been modified by a modifier has relatively poor dispersibility in polyester due to the characteristic of easy agglomeration with nanopowders, which affects its cooling effect.
[0140] By comparing Example 1 with Comparative Examples 1 to 3, we can find that graphene has a higher thermal conductivity than boron nitride, so the cooling coefficient of the corresponding fabric is also higher. Increasing the content of graphene in the modified cooling agent can also increase the instantaneous cooling coefficient. However, simply blending and adding graphene and boron nitride powders has poor dispersibility, and the instantaneous cooling coefficient decreases instead of increases.
[0141] 3. Light absorption and heating performance test
[0142] The test method refers to Appendix B of T / GDBX 021-2019, and the judgment basis is T / GDBX 012-2019. The temperature rise calculation is: 20-minute temperature rise value = 20-minute temperature - initial temperature, 20-minute temperature difference = 20-minute test sample temperature - 20-minute control sample temperature; the control sample is the cotton standard lining specified in GB / T 7568.2. Judgment requirements: If the 20-minute temperature difference between the test sample and the control sample is greater than 5°C, it has a light-absorbing heat-generating effect.
[0143] The test results of Examples 1 to 5 and Comparative Examples 1 to 5 are shown in Table 3.
[0144] Table 3 Test results of light absorption and heat generation of Examples 1 to 5 and Comparative Examples 1 to 5
[0145] name Judgment result Example 1 none Example 2 none Example 3 none Example 4 none Example 5 none Comparative Example 1 none Comparative Example 2 have Comparative Example 3 have Comparative Example 4 have Comparative Example 5 none
[0146] It can be found from Table 3 that the fabric prepared by graphene fiber has a light absorption and heating effect. By comparing Example 2 and Comparative Example 3, it can be found that when the mass ratio of graphene to boron nitride is 1:99, the functional fabric prepared by the hybrid method does not have a light absorption and heating effect, while the textile fabric prepared by simple blending has a light absorption and heating effect; By comparing Examples 1 and 2 and Comparative Example 4, it can be found that even if the inorganic powder is modified by physical hybridization and a modifier, when the graphene content is high (BN:C=97:3), a light absorption and heating effect will still occur.
[0147] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A cooling masterbatch, characterized in that: The cooling masterbatch is formed by melt extrusion granulation of polyester and cooling agent, wherein the mass ratio of polyester to cooling agent is 70-90:10-30; the cooling agent is obtained by adding a modifier to a powder mixture of carbon hybridized boron nitride obtained by hybrid drying of carbon material and boron nitride; the mass ratio of carbon material to boron nitride is 98-99.9:0.1-1.
2. The cool feeling masterbatch according to claim 1, characterized in that The modifier is any one of octadecylamine, stearic acid and a silane coupling agent.
3. The cool feeling masterbatch according to claim 2, characterized in that The content of the modifier is 0.1-2%wt% of the carbon hybridized boron nitride.
4. The cool feeling masterbatch according to claim 1, characterized in that The carbon material is at least one of graphene and carbon nanotubes.
5. The cool feeling masterbatch according to claim 1, characterized in that: The particle size of the cooling agent is 200nm-1.5um, or the particle size of the polyester is 50-60 meshes.
6. The cool feeling masterbatch according to claim 5, characterized in that: The particle size of the cooling agent is 400nm-1um.
7. A method for preparing a cooling masterbatch, comprising preparing the cooling masterbatch according to any one of claims 1 to 6, characterized in that: The following steps are involved: The carbon material and boron nitride are hybridized and dried in a mass ratio of 98-99.9:0.1-1 to obtain a powder mixture, which is added into a modifier solution, mixed and dried to obtain a cooling agent; The cooling agent and the polyester are dry-mixed in a mass ratio of 10-30:70-90, melted, and extruded into granules.
8. The method for preparing the cool feeling masterbatch according to claim 7, characterized in that: The steps of hybridizing and drying the carbon material and the boron nitride at a mass ratio of 98-99.9:0.1-1 to obtain a powder mixture, adding the mixture to the modifier solution, mixing and drying to obtain the cooling agent specifically include: Preparation: weigh the carbon material and boron nitride in proportion and put them into containers filled with anhydrous ethanol respectively; Dispersion: ultrasonically treat the carbon material and boron nitride in the container for 2 to 5 minutes respectively to obtain a carbon material dispersion and a boron nitride dispersion; Hybridization: mixing the carbon material dispersion and the boron nitride dispersion, adding anhydrous ethanol, and ultrasonically hybridizing for 10 to 30 minutes to obtain a hybrid dispersion; Drying and grinding: After distilling the hybrid dispersion and drying it, grinding it to obtain a powder mixture; Modification: put the above powder mixture into a corresponding dosage of the modifier solution, stir evenly, and obtain a mixed liquid; Grinding and drying: Add the above mixed liquid into the mixture and grind it, then use spray drying to obtain the cooling agent.
9. A cool feeling polyester fiber, characterized in that: The polyester chips and the cooling masterbatch are melt-blended to obtain a melt, and the melt is spun. The cooling masterbatch is any one of claims 1 to 6.
10. A cool polyester fiber fabric, characterized in that: The cool polyester fiber is spun from the cool polyester fiber described in claim 9.
Citation Information
Patent Citations
Polyester fibers
CN104178840A
Cool masterbatches, cool fibers, and preparation method and application of cool master batch
CN108794997A
Cited By
Super cool polyester fiber and preparation method thereof
CN119932748A
Moisture-absorbing and quick-drying polyester fabric and preparation method thereof
CN120401095A
Cool-feeling high-elastic fiber as well as preparation method and application thereof
CN120866969A
Graphene modified chinlon profiled fiber composite cool fabric as well as preparation method and application thereof
CN120889055A
Cool polyester composite filament with both cool feeling and cotton-like hand feeling and preparation method of cool polyester composite filament
CN122235864A